Sequential reaching in older adults: vibrotactile feedback improves preparation and movement control. - Mohammadalinezhad Kolahdouz, Saba; Malone, Quinn; Passmore, Steven R.; Marotta, Jonathan J.; Glazebrook, Cheryl M. (Frontiers in Aging Neuroscience, 2026)
Introduction: Age-related motor decline is particularly evident during complex movements that require sequencing and bimanual coordination. The one-target advantage (OTA), in which single-target movements are typically initiated faster than the first segment of a two-target sequence, provides a useful framework for assessing planning demands in older adults. Methods: We examined whether task complexity and brief auditory or vibrotactile feedback delivered at the first target contact influence sequential reaching performance in 24 older adults (67.46 ± 5.41 years). Participants completed one- and two-target reaching tasks under three feedback conditions (no feedback, auditory feedback, or vibrotactile feedback) across movement types varying in complexity, including extension, reversal, unimanual, and bimanual movement sequences. Outcome measures included movement preparation, movement execution, movement transitions, kinematic measures, and endpoint accuracy. Results: Vibrotactile feedback selectively improved performance by shortening reaction time in the unimanual extension task relative to one-target movements, effectively reversing the typical OTA pattern. Vibrotactile feedback also increased peak velocity and altered kinematic control during the second movement segment. In contrast, movement time to the first target remained unchanged, whereas movement time to the second target increased with task complexity and was longest during bimanual conditions. Endpoint accuracy and consistency remained stable across feedback and task conditions, indicating that the kinematic benefits of vibrotactile feedback did not occur at the expense of either endpoint accuracy or endpoint consistency. Discussion: Overall, brief vibrotactile cues enhanced movement preparation and kinematic control in older adults during sequential reaching, particularly under higher coordination demands.